Left Upper Lobar Agenesis Associated with Tracheal Trifurcation: A Case Report - Hyoung Seop Kim; Jeong Joo Woo; Jin Kyung An (대한영상의학회지, 2019)
Lobar agenesis is a rare congenital anomaly that is characterized by the absence of the lobar pulmonary artery, pulmonary vein, bronchi, and parenchyma. We encountered a unique case of a young male patient with agenesis of the left upper lobe with tracheal trifurcation into three bronchi, all arising at the carinal level. Complex tracheobronchial anatomy was explicitly demonstrated by three-dimensional CT reconstruction and virtual bronchoscopy. Left upper lobar agenesis associated with tracheal trifurcation is an extremely rare anomaly that, to the best of our knowledge, has not been previously reported.